MiR-122 overexpression alleviates oxygen–glucose deprivation-induced neuronal injury by targeting sPLA2-IIA - Yu, Yuanfang; Li, Pan; Chen, Mengyuan; Zhan, Wenfeng; Zhu, Ting; Min, Ling; Liu, Hao; Lv, Bo (Frontiers in Neurology, 2024)
Background Ischemic stroke (IS) is a neurological disease with significant disability and mortality. MicroRNAs were proven to be associated with cerebral ischemia. Previous studies have demonstrated miR-122 downregulation in both animal models of IS and the blood of IS patients. Nonetheless, the role and mechanism of miR-122-5p in IS remain unclear. Methods We established primary human and mouse astrocytes, along with HT22 mouse hippocampal neuronal cells, through oxygen–glucose deprivation/reoxygenation (OGD/R) treatment. To assess the impact of miR-122, we employed CCK8 assays, flow cytometry, RT-qPCR, western blotting, and ELISA to evaluate cell viability, apoptosis, reactive oxygen species (ROS) generation, and cytokine expression. A dual-luciferase reporter gene assay was employed to investigate the interaction between miR-122 and sPLA2-IIA. Results Overexpression of miR-122 resulted in decreased apoptosis, reduced cleaved caspase-3 expression, and increased cell viability in astrocytes and HT22 cells subjected to OGD/R. RT-qPCR and ELISA analyses demonstrated a decrease in mRNA and cytokine levels of interleukin (IL)-6 and tumor necrosis factor (TNF)-α in both astrocytes and HT22 cells following miR-122 overexpression. Moreover, miR-122 overexpression reversed OGD/R-induced ROS levels and 8-OHdG formation in astrocytes. Additionally, miR-122 overexpression decreased the mRNA and protein expression of inducible nitric oxide synthase (iNOS). Furthermore, we found that miR-122 attaches to the 3′-UTR of sPLA2-IIA, thereby downregulate its expression. Conclusion Our study demonstrates that miR-122-mediated inhibition of sPLA2-IIA attenuates OGD/R-induced neuronal injury by suppressing apoptosis, alleviating post-ischemic inflammation, and reducing ROS production. Thus, the miR-122/sPLA2-IIA axis may represent a promising target for IS treatment.